A Historical Study of Iraqi Paralympic Participations in IPC World Championships Athletics from 1990 till 2017 - Mohsen, Moqdad; Sabieh, Yessar (Journal of Physical Education, 2021)
The aim of the research is to document Iraqi Paralympic participations in IPC athletics from 1990 – 2017. The problem of the research lies in archives destruction in 2003 especially in athletics for the physically disabled thus all history is destroyed and it was necessary to document this history again. The researchers used the historical method to record the history of the sport and the subjects were physically disabled national league athletic participations from 1990 till 2019. The researchers concluded that all undocumented participation details in IPC from 1990 till 2017 were documented. Finally, they recommended paying attention to documenting Iraqi international participations on regular bases through special records and should be saved in the central Iraqi federation of athletics.